Association of smoking and ALK tyrosine-kinase inhibitors on overall survival in treatment-naïve ALK-positive advanced lung adenocarcinoma - Zheng, Zhe-Rong; Ku, Hsiu-Ying; Chen, Kun-Chieh; Chiang, Chun-Ju; Wang, Chih-Liang; Chen, Chih-Yi; Tsai, Chun-Ming; Huang, Ming-Shyan; Yu, Chong-Jen; Chen, Jin-Shing; Chou, Teh-Ying; Lee, Wen-Chung; et al. (Frontiers in Oncology, 2023)
Introduction: Lung cancer is the leading cause of cancer death worldwide.[1, 2] Mutations over several driver genes, such as epidermal growth factor receptor (EGFR), echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion mutations, Kirsten rat sarcoma viral oncogene homolog, and human EGFR 2, are known to be involved in the initiation and maintenance of lung adenocarcinoma.[3] Different kinds of driver gene mutations result in different clinical characteristics. EML4-ALK translocation is more common in younger patients and never-smokers.[4, 5] Further, the mutation can be detected in approximately 3-5% of non-small cell lung cancer (NSCLC) patients.[6] Several ALK tyrosine kinase inhibitors (TKIs), if administered as first-line treatment, can effectively suppress the oncogenic activity of ALK rearrangement and improve the outcomes of advanced ALK-positive lung cancer patients.[7-11] Crizotinib was the first agent approved as it improved the progression-free survival (PFS) compared with platinum-based chemotherapy.[10] Subsequently, several next-generation ALK-TKIs including alectinib, brigatinib and lorlatinib showed better PFS and intracranial efficacy compared with crizotinib in treatment-naïve setting.[7, 8, 12] Therefore, these were preferred first line therapy in treatment-naïve patients. However, no clinical trials direct compare second- and third- generation ALK-TKIs and no treatment sequence after first-line therapy was suggested. How to make the right choice is based on factors including systemic and intracranial efficacy of the ALK-TKIs, various EML4-ALK variants, mechanisms of resistance as well as the toxicity profile. Smoking is not only associated with lung cancer incidence, but also influences the efficacy of lung cancer treatment.[13] ALK-TKIs as first-line[10, 11, 14] or second-line[15] treatments show similar benefits of PFS in never-smokers and smokers, but overall survival (OS) is immature for most trials.[7-11] Meanwhile, the association of smoking and ALK-TKIs on OS of treatment-naïve ALK-positive advanced lung adenocarcinoma patients in the real world remains unclear. Thus, this study aimed to explore the epidemiology, clinical characteristics, and OS of treatment-naïve ALK-positive advanced lung adenocarcinoma patients, focusing on smoking status and ALK-TKIs treatment, using a nationwide cancer registry database in Taiwan.